Penerapan Pelaksanaan Kewirausahaan Di SMKN 1 Cijulang - Sidik, Japar (LPPM Universitas Bina Bangsa, 2022)
Entrepreneurship in education is a continuous effort by schools, especially school leaders, to make schools more qualified. This entrepreneurial spirit is about reading opportunities carefully, examining all elements of the institution to look for new and innovative, researching realistic and available resources, managing risks and well-being (making profits). (including striving to The problems with this scientific study are: 1) How is entrepreneurship education implemented in schools? From the observations and interviews it is clear that the application of entrepreneurial education can be developed through several activities such as: 2) through extracurricular activities; 3) through personal development; 4) changes in the implementation of entrepreneurship learning from theory to practice. 5) Integration of entrepreneurial education materials/textbooks. 6) Integrate entrepreneurial education through school culture. 7) Integration of entrepreneurship education with local content